Peran Mahasiswa Pariwisata Dalam Pengembangan Destinasi Wisata Air Terjun Batu Manarus Kecamatan Pahae Julu - Rut Irmawati Gultom; Benny Siringoringo (PANUNTUN (Jurnal Budaya, Pariwisata, dan Ekonomi Kreatif), 2026)
This study aims to analyze the role of tourism students in the development of the Batu Manarus Waterfall tourist destination in Pahae Julu District. The research employs a qualitative approach using a descriptive method. Data were collected through observation, in-depth interviews, and documentation involving students, destination managers, local government officials, the Tourism Awareness Group (Pokdarwis), and the local community. The findings indicate that students play strategic roles as innovators, facilitators, promoters, and conservation agents. As innovators, students generate creative ideas for tourism product development and digital promotion. As facilitators, they bridge collaboration among the community, the government, and destination managers through mentoring and educational activities. As promoters, students utilize social media and various communication channels to enhance the image and appeal of Batu Manarus Waterfall. As conservation agents, they contribute to environmental preservation and raise public awareness regarding the importance of sustainable tourism.